SOCIAL IMPACT OF PROJECT IMPLEMENTATION FOR SUSTAINABILITY: A CASE STUDY OF FLYOVER CONSTRUCTION WITHIN BAUCHI METROPOLIS - Nimchak, K. G.; Bala, A. H.; Mohammed, I. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined social impact assessment (SIA) of project implementation for sustainability a case study of flyover construction in Bauchi metropolis, Nigeria. A multi-stage sampling technique was employed in selecting 200 respondents for the study. Data were collected using structured questionnaires and analyzed using descriptive statistics and Tobit regression. The results showed that majority (72.0%) of respondents were married, within the economically active age bracket of 35–44 years (40.0%), and had operated in the affected area for more than 10 years (42.5%). The results of the regression analysis revealed that educational level (P < 0.01) and impact on business (P<0.03) were the significant factors influencing vulnerability of the respondents to the effects of flyover construction. The study further revealed that economic challenges to effects of flyover were economic hardship (90.5%), loss of income (45.0%) and loss of business premises (31.0%). Similarly the constraints to effective implementation of the project were inadequate financial compensation (66.0%), lack of alternative business premises (59.0%), and poor relocation arrangements (48.5%). The study concludes that flyover construction has social impact on livelihood restoration, stakeholder engagement, and compensation mechanisms and it is influenced by educational level and impact on business. In view of the constraints highlighted the study recommends the conduction of formal SIA, community engagement, timely and fair compensation, provision of alternative trading spaces, and capacity-building programs for affected business owners by the project implementation body.